Children gut microbiota exhibits a different composition and metabolic profile after in vitro exposure to Clostridioides difficile and increases its sporulation - Horvat, Sabina; Mahnic, Aleksander; Makuc, Damjan; Pečnik, Klemen; Plavec, Janez; Rupnik, Maja (Frontiers in Microbiology, 2022)
Clostridioides difficile (Clostridium difficile) infection (CDI) is one of the main public health concerns in adults, while children under 2 years of age are often colonized asymptomatically. In both adults and children, CDI is strongly associated with disturbances in gut microbiota. In this study, an in-vitro model of children gut microbiota was challenged with vegetative cells or a conditioned media of six different toxigenic C. difficile strains belonging to the ribotypes 027, 078, and 176. In the presence of C. difficile or conditioned medium the children gut microbiota diversity decreased and all main phyla (Bacteroidetes, Firmicutes, and Proteobacteria) were affected. The NMR metabolic spectra divided C. difficile exposed children gut microbiota into three clusters. The grouping correlated with nine metabolites (short chain fatty acids, ethanol, phenolic acids and tyramine). All strains were able to grow in the presence of children gut microbiota and showed a high sporulation rate of up to 57%. This high sporulation rate in combination with high asymptomatic carriage in children could contribute to the understanding of the reported role of children in C. difficile transmissions.